K∗(892)0 and ϕ(1020) production in Pb-Pb collisions at √sNN=2.76 TeV - Abelev, Betty; Angelov, Venelin; Busch, Oliver; Glässel, Peter; Klein, Jochen; Knichel, Michael Linus; Lohner, Daniel; Lu, Xianguo; Maire, Antonin; Oyama, Ken; Pachmayer, Yvonne C.; Reygers, Klaus; et al. (Physical review. C, Nuclear physics, 2015)
The yields of the K∗(892)0 and ϕ(1020) resonances are measured in Pb-Pb collisions at √sNN=2.76 TeV through their hadronic decays using the ALICE detector. The measurements are performed in multiple centrality intervals at mid-rapidity (|y|<0.5) in the transverse-momentum ranges 0.3<pT<5 GeV/c for the K∗(892)0 and 0.5<pT<5 GeV/c for the ϕ(1020). The yields of K∗(892)0 are suppressed in central Pb-Pb collisions with respect to pp and peripheral Pb-Pb collisions (perhaps due to rescattering of its decay products in the hadronic medium), while the longer-lived ϕ(1020) meson is not suppressed. These particles are also used as probes to study the mechanisms of particle production. The shape of the pT distribution of the ϕ(1020) meson, but not its yield, is reproduced fairly well by hydrodynamic models for central Pb-Pb collisions. In central Pb-Pb collisions at low and intermediate pT, the p/ϕ(1020) ratio is flat in pT, while the p/π and ϕ(1020)/π ratios show a pronounced increase and have similar shapes to each other. These results indicate that the shapes of the pT distributions of these particles in central Pb-Pb collisions are determined predominantly by the particle masses and radial flow. Finally, ϕ(1020) production in Pb-Pb collisions is enhanced, with respect to the yield in pp collisions and the yield of charged pions, by an amount similar to the Λ and Ξ.